The impacts of bronze age in the gene pool of Chinese: Insights from phylogeographics of Y-chromosomal haplogroup N1a2a-F1101 - Yu, Hui-Xin; Ao, Cheliger; Wang, Xiao-Peng; Zhang, Xian-Peng; Sun, Jin; Li, Hui; Liu, Kai-Jun; Wei, Lan-Hai (Frontiers in Genetics, 2023)
Previous studies of archaeology and history suggested that the rise and prosperity of Bronze Age culture in East Asia had made essential contribution to the formation of early state and civilization in this region. However, the impacts in perspective of genetics remain ambiguous. Genetic researches indicated the Y-chromosome Q1a1a-M120 and N1a2a-F1101 may be the two most important paternal lineages among the Bronze Age people in ancient northwest China. Here, we investigated the 9,000-years history of haplogroup N1a2a-F1101 with revised phylogenetic tree and spatial autocorrelation analysis. The initial differentiation location of N1a2a-F1101 and its most closely related branch, N1a2b-P43, a major lineage of Uralic-speaking populations in northern Eurasia, is likely the west part of northeast China. After ~4 thousand years of bottleneck effect period, haplgroup N1a2a-F1101 experienced continuous expansion during the Chalcolithic age (~ 4.5 kya to 4 kya) and Bronze age (~ 4 kya to 2.5 kya) in northern China. Ancient DNA evidence supported that this haplogroup is the lineage of ruling family of Zhou Dynasty (~ 3 kya-2.2 kya) of ancient China. In general, we proposed that the Bronze Age people in the border area between the eastern Eurasian steppe and northern China not only played a key role in promoting the early state and civilization of China, but also left significant traces in the gene pool of Chinese people.